2015
DOI: 10.3109/08941939.2015.1060280
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inflammatory and Regenerative Genes in a Model of Liver Ischemia/Reperfusion and Partial Hepatectomy

Abstract: In the present survey, a new I/R swine model was proposed and specific parameters were analyzed, revealing differences between the study groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that IR‐stressed livers can activate the acute inflammation response, which increases hepatocellular injury . A complex inflammatory program is engaged in liver IR injury, which is always accompanied with a large increase in cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that IR‐stressed livers can activate the acute inflammation response, which increases hepatocellular injury . A complex inflammatory program is engaged in liver IR injury, which is always accompanied with a large increase in cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…A rat model of segmental (70%) hepatic ischemia/ reperfusion was established as previously described (Shen et al, 2002;Athanasopoulos et al, 2016). Rats were anesthetized with pentobarbital sodium (40 mg/kg) through intraperitoneal injection.…”
Section: Ischemia/reperfusion Injury Modelmentioning
confidence: 99%
“…Despite the unanimity of data in rats and mice that both pre-and postconditioning will have a beneficial effect to the liver I/R injury via modifications of the NO pathway (24)(25)(26)(27), there are conflicting data in the literature in regard to iNOS and eNOS expression in pigs during the early hours of reperfusion. These conflicting data consist to either failure to identify significant differences in the expression of iNOS during the early hours of reperfusion following hepatectomy in pigs (28) or even reports of minimal protection of the ischemic preconditioning all together (29). A significant experimental difference between studies undertaken in pigs and rodents (e.g., mice and rats) is the need of venous decompression of the intrabdominal viscera in pigs during the occlusion of the porta hepatis; this can be achieved either by a portocaval shunt (28) or veno-venous bypass (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting data consist to either failure to identify significant differences in the expression of iNOS during the early hours of reperfusion following hepatectomy in pigs (28) or even reports of minimal protection of the ischemic preconditioning all together (29). A significant experimental difference between studies undertaken in pigs and rodents (e.g., mice and rats) is the need of venous decompression of the intrabdominal viscera in pigs during the occlusion of the porta hepatis; this can be achieved either by a portocaval shunt (28) or veno-venous bypass (29,30). Pigs are unable to tolerate continuous prolonged occlusion of the portal vein as they develop quickly significant intestinal congestion with subsequent severe haemodynamic instability (30).…”
Section: Discussionmentioning
confidence: 99%